2000
DOI: 10.1086/313984
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Invasive Pneumococcal Infections in German Children Preventable by Pneumococcal Conjugate Vaccines

Abstract: The incidence and serotype distribution of Streptococcus pneumoniae as a cause of invasive diseases are unknown with regard to most European countries. From January 1997 through December 1998, population-based nationwide prospective surveillance was undertaken for invasive pneumococcal disease (IPD) in children in Germany, based on monthly independent reports from all pediatric hospitals and from clinical microbiology laboratories. On the basis of 896 reported IPD cases (including 404 with meningitis), the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
3
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 25 publications
7
54
3
4
Order By: Relevance
“…Since several studies have demonstrated a cross-reactive effect against serotype 6A, we assume a cumulative rate of coverage of the conjugate vaccine of 83% (7,32). These data are comparable to those found in studies conducted in Europe and the United States, where rates of coverage of 60 to 80% are expected (17,19,21,31,33,39).…”
Section: Discussionmentioning
confidence: 61%
“…Since several studies have demonstrated a cross-reactive effect against serotype 6A, we assume a cumulative rate of coverage of the conjugate vaccine of 83% (7,32). These data are comparable to those found in studies conducted in Europe and the United States, where rates of coverage of 60 to 80% are expected (17,19,21,31,33,39).…”
Section: Discussionmentioning
confidence: 61%
“…For countries with high blood culturing rates, and therefore a high proportion of non-meningitis IPD, aggregate estimates of PCV impact on IPD may mask a differential effect on meningitis IPD. Meningitis IPD, however, has a higher clinical relevance and public health impact because case fatality and sequelae rates are about fourfold higher than for non-meningitis IPD [6].…”
Section: Discussionmentioning
confidence: 98%
“…Although chance might be another explanation, given the wide 95% CIs of the IRRs, biological explanations related to the tropism of different pneumococcal serotypes appear more likely: German data collected in 1997-98 (during the pre-vaccination period) showed an about equal incidence of meningitis and non-meningitis IPD for serotypes 6A, 7F and 19A, whereas the incidence of serotypes 1, 3 and 5 was significantly higher in non-meningitis than in meningitis IPD [6]. A similar pattern was observed after the introduction of PCV in 2007 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the true incidence might be twice as high because eSPed does not capture all cases as shown by capture-recapture analyses. 17,18 Comparing this incidence with the overall reported incidence of rV disease in the same age group in germany (115/10,000), 1 a vsrVd occurs in about 1% of all reported rV cases in children under 5 years of age. 19 the median duration of hospitalization (6 days) is considerably longer than the median duration of all reported hospitalized rV cases (2-3 days).…”
Section: Discussionmentioning
confidence: 72%